2021
DOI: 10.1557/s43580-021-00102-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the interface layer on the cycling behaviour and retention of ferroelectric hafnium oxide

Abstract: Reliability is a central aspect of hafnium oxide-based ferroelectric field effect transistors (FeFETs), which are promising candidates for embedded non-volatile memories. Besides the device performance, understanding the evolution of the ferroelectric behaviour of hafnium oxide over its lifetime in FeFETs is of major importance for further improvements. Here, we present the impact of the interface layer in FeFETs on the cycling behaviour and retention of ferroelectric silicon-doped hafnium oxide. Thicker inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…As shown recently [38], the annealing temperature strongly influences the electrical behavior. While low annealing temperatures, e.g.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…As shown recently [38], the annealing temperature strongly influences the electrical behavior. While low annealing temperatures, e.g.…”
Section: Resultsmentioning
confidence: 67%
“…1c) have revealed that even for the ferroelectric-like wakeup, as observed in Fig. 1b, purely ferroelectric behavior is not present initially [38]. This is indicated by the peak splitting in the extracted Preisach density.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations